ANALISIS PEMBELAJARAN AKTIF BERBASIS KETERAMPILAN ABAD 21 PADA GURU MI DI KOTA SEMARANG - Kristi Liani Purwanti; Zuanita Adriyani; Ega Fatmawati (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
This study aims to analyze the implementation of 21st century skills-based active learning at partner MI of UIN Walisongo Semarang after obtaining training and mentoring since 2018. This study is a qualitative field research with fourth grade teachers at partner MI of UIN Walisongo Semarang as the subjects. The partner MI of UIN Walisongo are MI Nashrul Fajar, MI Taufiqiyah, MI Tarbiyatul Khairat, MI Al Khoirriyah 02 and MI Al Hikmah. Data collection techniques were carried out through an observation of the learning process, the documentation of reviewing the lesson plan and worksheets as well as interviews. Data analysis in this study consists of data reduction, data presentation, and drawing conclusions. The conclusion shows that critical thinking indicators are not distinguishable in the lesson plan as the teacher has not given students the opportunity to explain their mind in their own language. The indicators of collaboration and communication have not been implemented optimally in the learning process. This is because it is not possible to have discussions or close interactions during the pandemic, students were keeping their distance from each other while paying attention to health protocols. In addition, the majority of communication indicators that are implemented tend to be the results of individual work, not the results of discussions. The submission of the learning conclusions is more likely to be delivered by the teacher at the end of the learning process, not delivered by students directly. Indicators of creativity and critical thinking have not been appeared optimally in the worksheets. In the worksheets, the teacher has not given the freedom for students to determine how to complete the task and has not provided the assignments that require students' creativity. Questions given by teachers mostly only require students to repeat the ideas or material from the teacher rather than producing students' own ideas.